Pemberdayaan Masyarakat Pesisir dalam Meningkatkan Nilai Tambah Melalui Inovasi Mesin Pengering Ikan dan Pemasaran Secara Online di Desa Lampulo Kecamatan Kuta Alam Kota Banda Aceh - Mujiburrahmad; Juanda; Sukhairi , T. Arriessa (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
The problems that exist in partners are: 1). Lack of knowledge and skills of partners in producing dryer innovation, 2). Lack of knowledge about good quality management, 3). Not understanding the concept of product packaging, 4). Not yet understanding how to market online and professionally, 5). Not yet understanding the business management system and correct bookkeeping administration. Implementation activities will begin with the coordination and outreach stage with partners for implementing activities, then continue with the provision of drying oven machines and training on their use. Followed by good quality management training by introducing GMP (Good Manufacturing Practices) and SSOP (Sanitation standard operating procedures). Furthermore, partners will be facilitated in creating a marketing platform and training in its use to make the marketing process easier. The final activity is providing counseling regarding correct business management, administration and bookkeeping as well as evaluating the activities that have been carried out. The conclusions of the implementation of community service activities in Lampulo Village, Kuta Alam District, Banda Aceh City are: (1) Availability of drying equipment (ovens) using LPG fuel, as well as an increase in woodfish production, especially during the rainy season, by 30%. (2) Increased knowledge, skills, and abilities of partners in applying GMP and SSOP (100%). (3) Increasing partners' knowledge, skills, and abilities regarding product packaging manufacturing (Pakcakging). (4) Availability of a marketing platform that can be used by partners (100%). (5) There is an increase in knowledge, skills and abilities in understanding business management and ways to develop it (100%).